2023
DOI: 10.3390/en16010570
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Aspect Ratio and Cross-Sectional Area of Rectangular Tubes on Packing Characteristics of Mono-Sized Pebble Beds

Abstract: The packing characteristics of a pebble bed are essential to understand the heat- and mass-transfer processes occurring within a granular system. Therefore, the packing characteristics of rectangular prismatic pebble beds randomly packed with mono-sized pebbles are analyzed. In terms of the average and local packing fraction distribution, coordination number, and radial distribution function, the effects of the rectangular tube aspect ratio and cross-sectional area on the packing properties of pebble beds are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 62 publications
(103 reference statements)
0
0
0
Order By: Relevance
“…Rahman presented correlations for a cylindrical packed bed filled with monosized pebbles for different aspect ratios. The result agrees with the work of Gong et al on spherical pebbles in a rectangular duct. From the above discussion, it can be concluded that the average porosity (Ø) of the packed bed remains constant even when the model is scaled since Ø is only a function of aspect ratio.…”
Section: Scale Analysis For Cartesian Coordinate Systemssupporting
confidence: 93%
“…Rahman presented correlations for a cylindrical packed bed filled with monosized pebbles for different aspect ratios. The result agrees with the work of Gong et al on spherical pebbles in a rectangular duct. From the above discussion, it can be concluded that the average porosity (Ø) of the packed bed remains constant even when the model is scaled since Ø is only a function of aspect ratio.…”
Section: Scale Analysis For Cartesian Coordinate Systemssupporting
confidence: 93%